Elastic trapping by acoustoelastically induced transparency - Dongwoo Lee; Jeonghoon Park; Seokwoo Kim; Beomseok Oh; Xianji Piao; Namkyoo Park; Junsuk Rho (Communications Physics)
Abstract Elastic bound states in the continuum (BICs) have recently attracted significant interests due to their exceptionally high-Q-factor, which enables  the confined mode to be completely decoupled from spectrally coexisting radiative channels. We report on the emergence of a state that induces a slow vibration phenomenon, which exhibits a multiphysics analogy to the notion of slow light observed in electromagnetically induced transparency (EIT). Such a state can be achieved through the interaction of acoustoelastic coupling. Our proposed design involves a composite with two acoustic cavities encased in an elastic bar, making quasi-BICs feasible with high spatial efficiency in a localized area while allowing for the tunability of the Purcell factor by around six orders of magnitude. The observation of quasi-BICs with acoustoelastically induced transparency (AEIT) lineshapes, which are manifested by the coupling of two disparate physics domains, will expand the BIC family and enable applications in areas such as lasing, sensing, screening, and energy storage platforms where ultrahigh-Q-factor modes and radiative channels coexist.